Deposition of aluminium silicate film on diamond by sol-gel techniques. (May 2015) - Wang, Y. Z.; Liang, B. Y.; Zhang, W. X.; Liu, J. L.
Abstract : Diamond particles were coated with aluminium silicate film by sol-gel techniques, and characterised by X-ray diffraction, scanning electron microscope, energy-dispersive spectroscope and Differential Scanning Calorimetry and Thermogravimetric Analysis (DSC-TG). It was shown that amorphous aluminium silicate thin film was obtained, which encapsulated the diamond particles completely. As a good barrier, this film protected the diamond with enhanced oxidation resistance. Specifically, the initial oxidation temperature of the aluminium silicate film-coated diamond in air atmosphere was 715°C, 85°C higher than that of the uncoated diamond.